Frequency specific activity in subthalamic nucleus correlates with hand bradykinesia in Parkinson's disease. - Tan, H; Pogosyan, A; Anzak, A; Foltynie, T; Limousin, P; Zrinzo, L; Ashkan, K; Bogdanovic, M; Green, A; Aziz, T; Brown, P (2013)
Local field potential recordings made from the basal ganglia of patients undergoing deep brain stimulation have suggested that frequency specific activity is involved in determining the rate of force development and the peak force at the outset of a movement. However, the extent to which the basal ganglia might be involved in motor performance later on in a sustained contraction is less clear. We therefore recorded from the subthalamic nucleus region (STNr) in patients with Parkinson's disease (PD) as they made maximal voluntary grips. Relative to age-matched controls they had more rapid force decrement when contraction was meant to be sustained and prolonged release reaction time and slower rate of force offset when they were supposed to release the grip. These impairments were independent from medication status. Increased STNr power over 5-12 Hz (in the theta/alpha band) independently predicted better performance-reduced force decrement, shortened release reaction time and faster rate of force offset. In contrast, lower mean levels and progressive reduction of STNr power over 55-375 Hz (high gamma/high frequency) over the period when contraction was meant to be sustained were both strongly associated with greater force decrement over time. Higher power over 13-23 Hz (low beta) was associated with more rapid force decrement during the period when grip should have been sustained, and with a paradoxical shortening of the release reaction time. These observations suggest that STNr activities at 5-12 Hz and 55-375 Hz are necessary for optimal grip performance and that deficiencies of such activities lead to motor impairments. In contrast, increased levels of 13-25 Hz activity both promote force decrement and shorten the release reaction time, consistent with a role in antagonising (and terminating) voluntary movement. Frequency specific oscillatory activities in the STNr impact on motor performance from the beginning to the end of a voluntary grip.